Epidemiology of stillbirth in low-middle income countries: A Global Network Study - McClure, Elizabeth M. (2011)
Objective. To determine population-based stillbirth rates and to determine whether the timing and maturity of the stillbirths suggest a high proportion of potentially preventable deaths. Design. Prospective observational study. Setting. Communities in six low-income countries (Democratic Republic of Congo, Kenya, Zambia, Guatemala, India, and Pakistan) and one site in a mid-income country (Argentina). Population. Pregnant women residing in the study communities. Methods. Over a five-year period, in selected catchment areas, using multiple methodologies, trained study staff obtained pregnancy outcomes on each delivery in their area. Main outcome measures. Pregnancy outcome, stillbirth characteristics. Results. Outcomes of 195 400 deliveries were included. Stillbirth rates ranged from 32 per 1 000 in Pakistan to 8 per 1 000 births in Argentina. Three-fourths (76%) of stillbirth offspring were not macerated, 63% were ≥37 weeks and 48% weighed 2 500g or more. Across all sites, women with no education, of high and low parity, of older age, and without access to antenatal care were at significantly greater risk for stillbirth (p<0.001). Compared to those delivered by a physician, women delivered by nurses and traditional birth attendants had a lower risk of stillbirth. Conclusions. In these low-middle income countries, most stillbirth offspring were not macerated, were reported as ≥37 weeks’ gestation, and almost half weighed at least 2 500g. With access to better medical care, especially in the intrapartum period, many of these stillbirths could likely be prevented.